Innovations in Digital Human Resource Management (International Journal of Food and Nutritional Sciences, 2022)
This article discusses the role of Innovation in digital HRM in organization to facilitate innovation in digital world of organizations where the force of inertia, standard ways of addressing problems and hierarchical communication patterns, inhibits innovation in organizations. Organization Innovation is based on knowledge from behavioral science disciplines such as psychology, sociology, anthropology, systems theory, organizational behavior, organization theory, and management. Behavioral science also including micro concepts, such as leadership, group dynamics and work design, and macro approaches such as strategy, organization design and international relations.